COVID-19 … What are drugs and strategies now? - Bellini, Valentina; Cortegiani, Andrea; Vetrugno, Luigi; Potì, Francesco; Saturno, Francesco; Craca, Michelangelo; Bignami, Elena (Acta Biomedica Atenei Parmensis, 2021)
From February 2019 the World faces the Covid19 pandemic. The data in our possession are still insufficient to effectively combat this pathology.The gold standard for diagnosis remains molecular testing, while clinical and instrumental and serological diagnostics are highly nonspecific leading to a slowdown in the battle against covid19.[3]Can Artificial Intelligence (AI) and Machine Learning (ML) help us? The use of large databases to cross-reference data to stratify the diagnostic scores, to quickly differentiate a critical Covid-19 patient from a non-critical one is the challenge of the future. All to achieve better management of resources in the field and a more effective therapeutic approach.[2]